The Development of Democracy in Developing Countries: A Literature Review - Samsidar Samsidar (Pt. Anagata Sembagi Education, 2024)
This study aims to examine the development of democracy in developing countries through a qualitative approach based on literature. Democracy in developing countries exhibits diverse dynamics, ranging from institutional progress to decline due to covert authoritarian practices. By reviewing various scientific sources such as academic journals, international agency reports, and reference books, this study presents a thematic synthesis of factors influencing the democratization process. The results indicate that the weakness of political institutions, elite dominance, and socio-economic inequality are the main obstacles to democratic consolidation. However, there is also a significant role for non-state actors such as civil society organizations and the media in promoting political openness and accountability. Furthermore, this study emphasizes the importance of a contextual, non-universal theoretical approach in understanding democratic practices in developing countries. These findings reinforce the urgency of developing a more inclusive, adaptive, and local-reality-based democratic framework. Thus, this literature study not only provides theoretical contributions to the realm of political science and governance but can also serve as a reference for formulating more sustainable policies to strengthen democracy in developing countries.